SURG-04. THE CLINICAL COURSE AND ROLE OF SURGERY IN PEDIATRIC MALIGNANT PERIPHERAL NERVE SHEATH TUMORS: A DATABASE STUDY. (12th November 2021) - Lu, Victor; Wang, Shelly; Daniels, David; Spinner, Robert; Levi, Allan; Niazi, Toba
Abstract: BACKGROUND: Malignant peripheral nerve sheath tumors (MPNST) are rare tumors found throughout the body, with their clinical course in children still to be completely understood. Correspondingly, this study aimed to determine survival outcomes and specific clinical predictors of survival in this demographic from a large national database. METHODS: All MPNST patients aged ≤18 year in the U.S. National Cancer Database (NCDB) between 2005-2016 were retrospectively reviewed. Data were summarized and overall survival (OS) was modeled using Kaplan-Meier and Cox regression analyses. RESULTS: A total of 251 pediatric MPNST cases were identified. Overall, mean age at diagnosis was 13.1 years (range, 1-18) with there being 132 (53%) females and 119 (47%) males. There were 84 (33%) MPNSTs located in extremities, 127 (51%) less than 1cm in size, and 22 (9%) have metastasis at diagnosis. In terms of treatment, surgery was pursued in 187 (74%) patients, chemotherapy in 116 (46%) patients, and radiation therapy in 129 (61%) patients. Five-year overall survival was estimated to be 52% (95% CI, 45-59%), and with median survival of 64 months (range, 36-136). Multivariate regression revealed older age (HR 1.10, P< 0.01), with metastases at time of diagnosis (HR 2.14, P=0.01), and biopsy only (HR 2.98, P< 0.01) all significantly and independently predicted shorter overall survival. Chemotherapy and radiation therapy were not statistically significant. CONCLUSIONS: Pediatric MPNSTs are rare malignant entities, and only approximately half of patients will survive to five years. There remains a clear survival benefit in pursuing maximal safe resection in these patients. As such, judicious workup with meticulous surgical resection by an expert team should then be considered the standard of care for these tumors in children.